First Combined in Vivo X-Ray Tomography and High-Resolution Molecular Electron Paramagnetic Resonance (EPR) Imaging of the Mouse Knee Joint Taking into Account the Disappearance Kinetics of the EPR Probe - Nicolas Bézière; Christophe Decroos; Karen Mkhitaryan; Elizabeth Kish; Frédéric Richard; Stéphanie Bigot-Marchand; Sylvain Durand; Florence Cloppet; Caroline Chauvet; Marie-Thérèse Corvol; François Rannou; Yun Xu-Li; et al. (Molecular Imaging)
Although laboratory data clearly suggest a role for oxidants (dioxygen and free radicals derived from dioxygen) in the pathogenesis of many age-related and degenerative diseases (such as arthrosis and arthritis), methods to image such species in vivo are still very limited. This methodological problem limits physiopathologic studies about the role of those species in vivo, the effects of their regulation using various drugs, and the evaluation of their levels for diagnosis of degenerative diseases. In vivo electron paramagnetic resonance (EPR) imaging and spectroscopy are unique, noninvasive methods used to specifically detect and quantify paramagnetic species. However, two problems limit their application: the anatomic location of the EPR image in the animal body and the relative instability of the EPR probes. Our aim is to use EPR imaging to obtain physiologic and pathologic information on the mouse knee joint. This article reports the first in vivo EPR image of a small tissue, the mouse knee joint, with good resolution (≈ 160 μm) after intra-articular injection of a triarylmethyl radical EPR probe. It was obtained by combining EPR and x-ray micro-computed tomography for the first time and by taking into account the disappearance kinetics of the EPR probe during image acquisition to reconstruct the image. This multidisciplinary approach opens the way to high-resolution EPR imaging and local metabolism studies of radical species in vivo in different physiologic and pathologic situations.